Application of Environmental, Social, and Governance (ESG) Principles as Dynamic Capabilities: A Case Study of PT Mustika Ratu Tbk - Rahma Muti’ah; Mulkan Ritonga; Nurintan Asyiah Siregar (ProBisnis : Jurnal Manajemen, 2026)
This study aims to analyze the implementation of Environmental, Social, and Governance (ESG) principles at PT Mustika Ratu Tbk (MRAT) as a dynamic capability that builds a resilient, responsible, and sustainable financial system. Using a qualitative approach with a single case study design, secondary data were collected through library research on 19 international journal articles (2025–2026) and documentation study of annual reports, sustainability reports, press releases, and national media coverage for the 2023–2026 period. Deductive thematic content analysis was conducted by classifying empirical evidence into the ESG principle framework: dynamic materiality, stakeholder orientation, long-term value creation, transparency and accountability; along with E, S, G dimensions; implementation instruments; key actors; and impacts. The results show that MRAT consistently actualizes the four main ESG principles through programs such as mangrove planting, Women Empowerment Conference, Jamunomic Ecosystem, and ISO 9001 and ISO 14001 certifications. The governance dimension (G) proves to be the foundation enabling the effectiveness of environmental (E) and social (S) dimensions. Policy, market, internal governance, and digital instruments are integrated synergistically, with digital transformation acting as a mediator of performance improvement. The five key actors (management, investors, regulators, employees/partners, consumers/public) work harmoniously to create a virtuous circle of ESG reinforcement. The impacts include economic resilience, reduction of environmental and social risks, inclusive growth, and tangible contribution to intergenerational welfare. This study contributes to ESG literature in the context of local wisdom-based family firms in developing countries and provides a best practice model for similar companies.